Murphy, Peter. Interview with Margaret Bennett in Antigonish, NS. - Bennett, Margaret (2006)
An audio clip of Peter Murphy talking to Margaret Bennett in Antigonish about Newfoundland. They talk about music and how it relates to social history and passes stories down through generations.